2022
DOI: 10.3390/antiox11071241
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Redox Status in Military Pilots during Hypoxic Flight-Simulation Conditions—A Pilot Study

Abstract: At high altitude conditions, the low-pressure atmospheric oxygen reduces the generation of energy, thus inducing a decrease in oxygen availability. As a result, endurance flights evoke imbalance in redox signaling, posing a safety risk for the pilots involved. The aim of the present study was to assess changes in the redox status of military pilots during flight simulation conditions according to their flight hours (experts vs. novice). A total of seven expert pilots and an equal number of novice pilots (train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Our results confirm, in some way, the outcomes of former studies concerning military flight operations from members of our work group [7], who showed that flight operators with higher inflammatory biomarkers have a higher tendency to develop signs of chronic fatigue, but that these higher levels of inflammatory biomarkers cannot be, or are only in part, causally related to the number of performed flights and level of hypobaric hyperoxia. In fighter pilots in hypobaric hypoxic conditions, it seems that glutathione and three other oxidative stress markers increased with a higher tendency of oxidative stress elevation in experienced fighter pilots with more flight hours [25]. This could lead to two assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm, in some way, the outcomes of former studies concerning military flight operations from members of our work group [7], who showed that flight operators with higher inflammatory biomarkers have a higher tendency to develop signs of chronic fatigue, but that these higher levels of inflammatory biomarkers cannot be, or are only in part, causally related to the number of performed flights and level of hypobaric hyperoxia. In fighter pilots in hypobaric hypoxic conditions, it seems that glutathione and three other oxidative stress markers increased with a higher tendency of oxidative stress elevation in experienced fighter pilots with more flight hours [25]. This could lead to two assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Petraki et al assessed the effects of a flight simulation on the antioxidative status (total antioxidant capacity—TAC, CAT, and GSH) as well as the oxidative modifications of proteins and lipids through the measurement of protein carbonyls (PCs) and thiobarbituric acid reactive species (TBARS) of military pilots with differing flying experiences. They observed an adaptation to the flight training in an effort to battle oxidative stress in experienced pilots, revealed by increased levels of GSH [ 58 ]. Corsi et al proposed erythrocyte glycohydrolases as new sensitive markers to assess oxidative stress, and they investigated their concentration in air force pilots.…”
Section: Oxidative Stressmentioning
confidence: 99%